Pengembangan Desa Wisata Jatimalang Berbasis Industri Kreatif - Budi Setiawan; . Zulfanita (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
The purpose of this activity is to develop tourism village Jatimalang to improve community empowerment in the management of tourism potential. Community service activities through the Field Work Experience Learning Community Empowerment (KKN PPM) develop coastal resorts Jatimalang become an attractive tourist destination area and able to empower the local community-based development of creative economy. KKN PPM using the method of Education for Sustainable Development (EfSD) is one method of community service oriented problem solving in the community. EfSD method emphasizes the three pillars, namely economic, ecological or environmental, and social. Program development activities carried out in outline included the development of tourist attractions, accessibility, amenitas, and tourism activities.